Women, media and sport : challenging gender values - Creedon, Pamela J. (Sage, 1994)
This title links women, sports, and the mass media with feminist perspectives from history, psychology, women's studies, sociology, kinesiology, and mass communication. The volume is divided into three parts: overview and definitions (7 chapters) cultural contexts and gender values (3 chapters); and developing a new sports model (3 chapters).